Type 3 Innate Lymphoid Cells as Regulators of the Host-Pathogen Interaction - Valle-Noguera, Ana; Ochoa-Ramos, Anne; Gomez-Sánchez, Maria José; Cruz-Adalia, Aranzazu (Frontiers in Immunology, 2021)
Type 3 Innate lymphoid cells (ILC3s) have been described as tissue-resident cells and characterized throughout the body, especially in mucosal sites and classical first barrier organs such as skin, gut and lungs, among others. A significant part of the research has focused on their role in combating pathogens, mainly extracellular pathogens, with the gut as the principal organ. However, some recent discoveries in the field have unveiled their activity in other organs, combating intracellular pathogens and as part of the response to viruses. In this review we have compiled the latest studies on the role of ILC3s and the molecular mechanisms involved in defending against different microbes at the mucosal surface, most of these studies have made use of conditional transgenic mice. The present review therefore attempts to provide an overview of the function of ILC3s in infections throughout the body, focusing on their specific activity in different organs.